Rantai Nilai Komoditas Kentang Granola di Desa Candikuning Kecamatan Baturiti Kabupaten Tabanan - SUKAYANA, I MADE; DARMAWAN, DWI PUTRA; WIJAYANTI, NI PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.3, Juli 2013, 2013)
ABSTRACT The Value Chain Of Granola Potatoes In The Candikuning Village, Sub-District Of Baturiti, Tabanan Regency The value chain of commodity of potetoes is all activities done to its distribution to the end consumers. The mean problems faced by the majority of horticultue farmers or long marketing distribution chain, obstacles in the supply of seeds, in ability to meet the consumer’s demands, the weakness of infrastructur, in adequate facilities, the unpredictable weather conditions, the perishable goods, and the price fluctuation. The objective of the study is to find out the value chain of commodity of potatoes in the Village of Candikuning, the Sub-district of Baturiti, Tabanan Regency. The production system that is carried out by the potato’s farmers starting from soil preparation to post harvest. The research findings show that there are four types of different marketing channels. The marketing margins for each type of marketing channels were also different. The first marketing channel margin was IDR 7.750 which was the biggest margin because of its lomger channel of distribution, while the smallest margin was for the fourth channel because of the shortest channel of distribution namely IDR.4.000. farmers are expected to make a stronger cooperation with the marketing institutions in order to get more information on price of product and to make a better coordination of product distribution to avoid price monopoly in the marketing channels of potatoes. Keyword : value chain, marketing channel, marketing margin and granola potatoes
Keywords: value chain, marketing channel, marketing margin, granola potatoes